Atrial Fibrillation in the Young: A Neurologist's Nightmare. (2nd April 2015) - Aggarwal, Nikhil; Selvendran, Subothini; Raphael, Claire E.; Vassiliou, Vassilios
Abstract : Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia seen in clinical practice with prevalence in excess of 33 million worldwide. Although often asymptomatic and until recently considered a "benign" arrhythmia, it is now appreciated that thromboembolism resulting from AF results in significant morbidity and mortality predominantly due to stroke. Although an arrhythmia more commonly affecting the elderly, AF can also occur in the young. This review focuses on the impact of AF in the younger population and discusses the dilemmas of managing younger patients with AF.